Migration Theoretisieren - Kraler, Albert; Parnreiter, Christof (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
The article gives a review and critical discussion of contemporary theories of migration. It investigates the political and social reasons for theorizing migration, the different contexts, which were important for the emerging approaches. Although this branch of research is so strongly influenced, the authors observe certain progress in migration theories.